The Interaction of Elongation Factor G with N-Acetylphenylalanyl Transfer RNA·Ribosme Complexes - Modolell, Juan (1973)
N-Acetyl-Phe-tRNA, nonenzymically bound to the acceptor site of Escherichia coli ribosomes, readily undergoes translocation in the presence of elongation factor (EF)-G and GTP. The translocated N-acetyl-Phe-tRNA, bound to the ribosomal donor site, prevents further interaction of EF-G with the ribosome, for it inhibits the GTP hydrolysis that takes place in the presence of EF-G and ribosomes and it decreases the formation of either the GDP·EF-G·fusidic acid·ribosome complex or the 5′-guanylylmethylenediphosphonate·EF-G·ribosome complex. Deacylation with puromycin of the donor site-bound N-acetyl-Phe-tRNA reverses these inhibitions, even though the tRNA(Phe) moiety remains bound to the ribosme. These results suggest that ribosomes complexed with messenger RNA and peptidyl-tRNA may be restricted in their ability to interact with EF-G to that part of the elongation cycle when peptidyl-tRNA is in the acceptor site, and deacylated tRNA in the donor site. Deacylation of the donor site-bound peptidyl-tRNA associated with peptide bond formation may control the interaction of EF-G with the ribosome.